ChemInform Abstract: Highly Enantioselective Hydrogenation of 2‐Substituted‐2‐alkenols Catalyzed by a ChenPhos—Rh Complex. Issue 17 (28th April 2014) - Wang, Quanjun; Liu, Xueying; Liu, Xian; Li, Bin; Nie, Huifang; Zhang, Shengyong; Chen, Weiping
Abstract A ChenPhos‐Ru complex is found to be the most enantioselective catalyst system for the asymmetric hydrogenation of a broad range of 2‐substituted‐2‐alkenols reported so far, probably due to a hydrogen‐bonding secondary interaction of the dimethylamino unit of the ligand with the hydroxyl group of the substrate.